Investigation of Shut-In Effect on Production Performance in Shale Oil Reservoirs With Key Mechanisms - Jia, Pin; Ke, Xianzhe; Niu, Langyu; Li, Yang; Cheng, Linsong (Frontiers in Earth Science, 2022)
With the continuous development of the petroleum resources, unconventional oil reservoirs such as shale oil and tight oil have gradually become a main development direction of oil reservoirs in various countries. The reserves of shale oil in China are huge, reaching 1.42×1011t, therefore China has a great development potential and prospects for exploitation. However, in the process of developing shale oil reservoirs, we encountered many problems, such as un-replenishment of formation pressure and low flowback rate. At this stage, the development technology of shale oil reservoirs cannot effectively solve these problems. The proposition of shut-in technology can effectively improve these problems in theory, but the current shut-in technology of shale reservoirs after fracturing in China is still in its infancy. There is no in-depth understanding of the mechanism of shut-in wells. In addition, the factors affecting the change of oil-water distribution during shut-in after fracturing are complex, mainly including reservoir permeability, capillary force, fracture stress sensitivity and reservoir damage. This paper investigates the mechanism of shut-in in shale reservoirs after fracturing, and summarizes the mechanism of the shut-in process. Then, a single well shut-in numerical simulation model is established for the three complex characteristics of spontaneous imbibition, fracture stress sensitivity, and reservoir damage, and the oil-water distribution and change laws of shut-in shale reservoirs after fracturing are analyzed. Finally, the numerical model is used to study the influence of reservoir permeability, capillary force, fracture stress sensitivity and reservoir damage on oil-water replacement, pressure increase and daily fluid production during shut-in. The research results show that the influence of reservoir permeability and capillary force is more obvious, and the influence of fracture stress sensitivity and reservoir damage is relatively small.